Technological and Economic Enhancement of Obsolescent Cogeneration Plants - B. V. Yakovlev; A. S. Grinchuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2008)
The paper considers methods of technical cogeneration plant enhancement of the Belarussian power system, improvement of operational efficiency of their basic equipment. Examples of the realized reconstructions and prospective projects which are either under realization or to be executed are given in the paper. The authors are making a comparative analysis of domestic experience and world-wide achievements.